Self-Counseling Reflection in the Dynamics of Adolescent Resilience within Broken-Home Families - Yuliyatun, Yuliyatun; Romadhon, Nafi`ah Ayu (Universitas Islam Negeri Sunan Kudus, 2026)
This study aims to explore the role of self-counseling in shaping the resilience of adolescents raised in broken-home families. Using a qualitative descriptive case study approach, this research examines the experiences of adolescents who have grown up in families characterized by parental separation and dysfunctional family relationships. Data were collected through in-depth interviews, observations, and life history documentation. The findings reveal that adolescent resilience develops dynamically through a series of psychological processes involving stressful experiences, coping strategies, and adaptation. The identified self-counseling capacities that support coping and adaptation include self-awareness, self-regulation, impulse control, optimism, problem-analysis skills, empathy, self-efficacy, and the enhancement of positive affect. These findings indicate that self-counseling serves as an internal psychological resource that enables adolescents to manage emotional distress, adapt to adverse family circumstances, and foster positive personal development.